Kesantunan Bahasa di Kampus STKIP PGRI Sidoarjo - Hikmah, Amimah; Sari, Lela; Khasanah, Mufidatul; Fikri, Mohammad; Rismayanti, Trinita; Nurhayati, Eni (Jurnal Bahasa dan Sastra, 2024)
This study aims to describe the language politeness of STKIP PGRI Sidoarjo students. This study uses a qualitative approach with descriptive methods. Some of the students lack awareness in terms of language politeness. From this study, researchers hope that STKIP PGRI Sidoarjo students always use polite language in every communication among each other in daily activity. The techniques used in data collection are free listening technique, recording technique, and note taking technique. The target is to find out the deviation of the principle of language politeness in learning activities in the choice of words and polite ways of speaking between lecturers and students.